Incorporation and Assessment of Portable Tablet Technology During a Patient Counseling Exercise. (June 2015) - Maidhof, William; Marziliano, Anthony; Gillespie, Marc
Background: The marriage of cutting-edge technology to the practice of pharmacy for the purpose of promoting patient safety and enhancing pharmacy workflow is an exciting and continuous evolution.Objective: To assess whether the incorporation of portable tablet technology into a mock patient counseling exercise enhances or detracts from the overall counseling experience.Methods: Second professional year Doctor of Pharmacy students enrolled in a pharmacy practice laboratory were randomly assigned to either a portable tablet or a desktop computer group. During patient counseling, students using the portable tablet were required to incorporate the device into the counseling session in addition to written notations; the desktop computer group was allowed to utilize only written notations. Surveys were developed and distributed to students and instructors following each counseling session. Survey data and numerical grades earned for each counseling session were collected and analyzed.Results: One hundred seventy-eight students participated in the study. Survey data revealed students in the portable tablet group were more satisfied with their patient counseling sessions, as well as more confident during their interactions. Instructor grading revealed similar earned numerical grades for both study groups. Instructors noted little or no difference between the groups with regard to counseling effectiveness; however, students in the portable tablet group appeared more engaged with their mock patients.Conclusion: Incorporation of a portable tablet during a patient education session did not detract from, and may have enhanced, the experience. However, the essential components of the pharmacist–patient interaction remain vital, and technology should not become the focus of the interaction.